Landscape and soundscape quality promote stress recovery in nearby urban nature: A multisensory field experiment - Korpilo, Silviya; Nyberg, Elina; Vierikko, Kati; Ojala, Ann; Kaseva, Janne; Lehtimäki, Jenni; Kopperoinen, Leena; Cerwén, Gunnar; Hedblom, Marcus; Castellazzi, Eugenia; Raymond, Christopher M. (Elsevier, 2024)
Cities have different benefits and risks, but are often stressful environments to live in. Everyday contact with nearby nature can be a crucial way to alleviate stress and increase the well-being of citizens. However, there is still limited evidence on how nature-health benefits vary according to the type and quality of natural environments. This study integrated multiple landscape and soundscape objective and perceived assessments to examine stress recovery in different types of neighbourhood nature. We used a field randomised experiment (n=45) to analyse effects of various random and fixed factors on restoration including: environmental conditions (e.g. temperature, wind, air quality), personal characteristics (e.g. age, gender, perceived health, nature connectedness), presence of other people and environmental quality (e.g. Perceived Environmental Aesthetic Qualities Scale and Perceived Sound Affective Quality scale). We found that physiological and psychological restoration is significantly greater in sites with higher visual (% visual natural elements) and acoustic (Normalized Difference Soundscape Index (NDSI)) naturalness i.e. the beach and forest, compared to the urban park (control site). Perceived landscape and soundscape quality were strongly associated with stress recovery, and these results were more pronounced for the soundscape. This highlights that soundscape quality assessments deserve more systematic attention in urban green infrastructure research and planning. Finally, we found important early evidence of reduction in Electrodermal activity (EDA) only within 3 minutes of nature exposure especially in the forest.
Keywords: EDA; psychological restoration; soundscapes; stress recovery; urban green and blue spaces